Cuantificación de lluvias usando el radar perfilador de banda Ka MIRA 35C - Valdivia Prado, Jairo Michael (2018)
Objective: In the present work, an algorithm for rainfall estimation is developed, based on clouds and precipitation radar profiler data, located on Laboratory of Atmospheric Microphysics and Radiation – LAMAR in Huancayo Observatory of Instituto Geofísico del Perú. Methods: The algorithm use Doppler spectra data (values of power and velocity) to calculate raindrop size distribution, and based on this several microphysical parameters are calculated. The estimated rainfall rate is assessed using rain gauge data from meteorological station for a period of five months. Results: The algorithm is able to give us information of drops size distribution, liquid water content, and rainfall rate. Underestimation of 12% with ±1.3 mm in hourly cumulates has been found, which are compensated in long-term periods. Conclusion: These results suggest that the technic is adequate for studies that involve rainfall quantification, such as satellite precipitation algorithms